Electricity Consumption Forecasting using ARIMA and LSTM - Sokolović, Živko; Milic, Sasa (Proceedings, Electrical engineering institute "Nikola Tesla", 2025)
Accurate load forecasting is essential for the reliable and efficient operation of modern power systems. This study presents a comparative analysis of two prominent forecasting models—Autoregressive Integrated Moving Average (ARIMA) and Long Short-Term Memory (LSTM)—to assess their effectiveness in predicting electricity consumption. Both models were developed and fine-tuned through hyperparameter optimization to ensure fair and optimal performance. The evaluation considered predictive accuracy, computational efficiency, and resource usage. While ARIMA demonstrated advantages in inference speed and model simplicity, the LSTM model consistently outperformed it in terms of forecasting accuracy and its ability to capture complex temporal dependencies. These findings underscore the importance of selecting appropriate models and tuning strategies for specific forecasting scenarios. The study highlights LSTM as a more suitable approach for applications that demand high accuracy and adaptability, and it provides a foundation for future research involving advanced or hybrid methods.